Business Plan For Del Media limited - Olotu, Osahon (2012)
The purpose of this business plan is to present the growth ambition of Del Media Limited. Del Media Limited is a start-up outdoor advertising company based in Lagos, Nigeria with plans to expand its frontiers into digital entertainment company delivering and broadcast services for African films through a dedicated online platform. The online distribution presence of Del Media Limited aims to help African movie content producers to distribute their content through its proposed Youtube channel and dedicated Video-on-Demand (VOD) platform which will be exclusively handled by a newly created division (Del Interactive) within Del Media Limited. Digital entertainment broadcast for African Diaspora is a fast growing market with the potential of reaching approximately 8 million online users. The purpose of this business plan is look at the short and mid-term strategies of Del Media Limited for its online film distribution platform using a web interface and third party interface (Youtube and Vimeo). The following issues were critically analysed with regards the evaluation of the business opportunity, key issues of structuring the business, major strengths and possible setbacks in implementation. The online platform has the potential of becoming the world's leading internet service for enjoying African movies. For a proposed subscription fee of US$5 a month, the registered users can instantly watch films streamed over the internet to PCs, Macs and TVs. Among the large and expanding base of devices for streaming movies online are internet-connected TVs, home theatre systems and internet video players; Apple iPhone, iPad and iPod touch, as well as Apple TV and Google TV which will be considered as future trends for the online movie distribution market as already embraced by established video-on-demand outfits (Netflix, Hulu and Lovefilm).